1990
DOI: 10.1136/hrt.63.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a high risk subgroup of patients with silent ischaemia after myocardial infarction: a group for early therapeutic revascularisation?

Abstract: Asymptomatic ("silent") ischaemia has been shown to be of prognostic significance in patients with stable and unstable angina and more recently in patients recovering after myocardial infarction. No therapeutic regimen has yet been shown to improve the prognosis of patients with silent ischaemia after infarction, which can be found in as many as a third of these patients. Attempts to achieve therapeutic revascularisation in all these patients may be undesirable, but early revascularisation could be especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Therefore, an estimate of the representatives of our population among infarct patients undergoing predischarge exercise stress testing cannot be made. However, the finding that more than half of our patients had silent myocardial ischemia is in agreement with previous studies [2, 3, 8]. In GISSI-2 data base 67% of more than 1,600 thrombolyzed AMI patients with positive exercise testing at 1 month had silent ischemia [3].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, an estimate of the representatives of our population among infarct patients undergoing predischarge exercise stress testing cannot be made. However, the finding that more than half of our patients had silent myocardial ischemia is in agreement with previous studies [2, 3, 8]. In GISSI-2 data base 67% of more than 1,600 thrombolyzed AMI patients with positive exercise testing at 1 month had silent ischemia [3].…”
Section: Discussionsupporting
confidence: 81%
“…Approximately 30% of patients undergoing exercise testing or ambulatory ECG monitoring early after thrombolyzed infarction have ST segment changes [2, 3, 8]. No registration of positive, negative or not diagnostic exercise tests in infarct patients eligible for randomization were included in the DANAMI protocol.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have compared the clinical characteristics of patients with angiographically documented coronary artery disease who have either silent or painful myocardial ischemia (Table 1; [22][23][24][25][26][27][28][29]. Although potential bias in the selection of patients for noninvasive testing cannot be excluded, these studies have not revealed any significant preponderance of diabetic subjects in the group with silent myocardial ischemia.…”
Section: Silent Coronary Artery Disease and Diabetesthementioning
confidence: 99%
“…One attractive way to evaluate the role of a defective anginal perceptual threshold as the cause of silent Ex-ECG = exercise electrocardiography, Th-201 = exercise thallium scintigraphy, Holter = ambulatory electrocardiogram monitoring, NA = not available [36] Ex-ECG 100 % 9 % (22 of 242) 9 % (54 of 600) Falcone et al [37] Ex-ECG 100 % 4 % (10 of 269) 6 % (12 of 204) Chipkin et al [38] Ex-ECG 48 % 14 % (14 of 101) 11 % (12 of 110) DeBelder et al [39] Ex-ECG 88 % 16 % (11 of 67) 8 % (3 of 37) Ouyang et al [40] Ex-ECG 100 % 24 % (9 of 38) 0 % (0 of 22) a Kurata et al [41] Th-201 66 % 24 % (26 of 108) 34 % (of 65) Hecht et al [42] Th-201 100 % 13 % (11 of 84) 32 % (9 of 28) a Gasperetti et al [43] Th Ex-ECG = exercise electrocardiography, Th-201 = thallium scintigraphy, NA = not available a p < 0.05 and b p < 0.001 for the comparison between the groups myocardial ischaemia is to measure the time interval from the emergence of ST segment changes to the onset of chest pain during exercise testing. Exercise electrocardiography done on 32 diabetic and 36 nondiabetic patients with angina pectoris showed that the diabetic patients experienced chest pain later after the onset of ST depression than the non-diabetic ones [48].…”
Section: Asymptomatic Coronary Artery Disease and Myocardial Ischaemimentioning
confidence: 99%